Long-latency auditory evoked potentials: Normalization of protocol applied to normal adults - Dayane Domeneghini Didone; Sheila Jacques Oppitz; Maiara Santos Goncalves; Michele Vargas Garcia (Archives of Otolaryngology and Rhinology - Peertechz Publications, 2019)
The clinical audiologist gained a strong ally in the diagnostic process of central auditory alterations from the association between electrophysiological and behavioral methods. The auditory evoked potentials refer to a series of electrical changes that occur from the inner ear to the cerebral cortex in response to sound stimulation [1], occurring in time (ms) and amplitude (μV) determined, thus enabling them to be classifi ed as short, medium and long latency potentials [2].